Isolation of a novel triterpene from the Essential oil of fresh leaves of Chromolaena odorata and its in-vitro cytotoxic activity against HepG2 cancer cell line - Velliangiri Prabhu and Subban Ravi (Journal of Applied Pharmaceutical Science)
The essential oil from the fresh leaves of Chromolaena odorata (Asteraceae) (L.) R.M. King & H. Rob. was obtained by hydro distillation. From the essential oil the compound (I) a triterpene derivative was isolated by column chromatography and it was characterized by IR, 1H-NMR, 13C-NMR and MS spectral data. It was screened for cytotoxicity against HepG2 by MTT assay. It showed significant cytotoxicity with IC50 value of 206.7 μg/ml towards HepG2 cancer cell line.
Keywords: Chromolaena odorata, IR, 1H-NMR, 13C-NMR,MS spectra, triterpene, Cytotoxicity.